Manajemen Blended Learning pada Mata Pelajaran PAK di SMP Negeri 1 Langowan - Bryan Kaurouw (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2024)
This study aims to describe and analyze blended learning management, especially in the subjects of Christian Religious Education (PAK) at SMP Negeri 1 Langowan, which includes planning, implementing, and evaluating blended learning. The research was conducted using a qualitative descriptive approach. The data obtained came from observations, interviews, and documentation studies. The results showed that: (1) Blended learning planning in PAK subjects at SMP Negeri 1 Langowan was carried out by designing learning according to situations and conditions, preparing learning supporting facilities and infrastructure, and preparing lesson schedules before the start of blended learning. (2) The implementation of blended learning in PAK subjects includes Synchronous blended learning (hybrid learning) which is carried out by combining 50% face-to-face learning and 50% online learning simultaneously and Blended learning-flipped classroom, namely face-to-face and online learning (teachers send assignments or learning materials online and provide reinforcement of material during face-to-face learning) which is carried out asynchronously at different times and places. (3) Evaluation of blended learning in PAK subjects, including evaluation of blended learning systems to evaluate any obstacles in blended learning, as well as efforts to overcome them and evaluation of blended learning outcomes of PAK subjects face-to-face and online through assessment of knowledge, attitudes, and skills, as well as formative and summative tests.